Relation Between Gut Brain Axis and Agni - Chande, Aarti; Shripathi , Acharya G; Changath, Sreelakshmy (International Research Journal of Ayurveda & Yoga, 2022)
"All diseases begin in the gut" - Hippocrates of Kos, this statement was made by Greek physician Hippocrates, regarded as the father of modern medicine1; although the importance of Agni (the digestive fire) has already been sold by Acharya charaka when he states that "the cause of all diseases is Mandagni" It has become evident that the intestinal bacteria and flora can affect the central nervous system (CNS) physiology and has an important role to play in the pathological conditions of the same. The nervous system and the gastrointestinal tract are communicating through a bidirectional network of signaling pathways called the gut-brain axis, which consists of multiple connections, including the vagus nerve, the immune system, and bacterial metabolites and products. It is clearly visible in the case of psychosomatic disorders like Ulcerative colitis, etc. that Gut is affected by Brain and vice-versa.